Optimal load shedding for microgrids with limited DGS (Application in Perwaja Steel Sdn Bhd) - Abd Rashid, Wan Norhisyam (2013)
Electric generation and transmission systems may not always meet peak demands. However, when the total demand is more than the generation, overall demand must be lowered, either by turning off service to some devices or cutting back the supply voltage in order to prevent uncontrolled service disruptions such as power outages or equipment damage. Utilities may impose load shedding on service areas via rolling blackouts or by agreements with specific high use industrial consumers to turn off equipment at times of system-wide peak demand. However it is quite different when this is applied on microgrids. Since microgrid is normally isolated from the main transmission line, therefore they have their own generation which is the distributed generation (DGs). DGs resources can include fuels cells, wind, solar or other energy sources. Distributed generation allows collection of energy from many sources and may give lower environmental impacts and improved security of supply. The multiple dispersed generation sources and ability to isolate the microgrid from a larger network would provide highly reliable electric power. Therefore, differential evolution (DE) is applied in a microgrid system in order to optimize the load shedding by reducing the total curtailed load. Direct Reduction (DR) Plant in Perwaja Steel Sdn Bhd. has its own microgrid system which is used to produce direct reduction iron (iron sponge). Load shedding is one of the security measures which are applied in the plant in to maintain the stability of the system. After the load shedding process, more cost is needed to restore the curtailed load. However, cost will be reduced if the total curtailed loads which are needed to be restored are reduced. Therefore DE is applied to reduce the total curtailed load in the DR Plant microgrid system.